Paraguay, Bhutan and Nepal: Landlocked but Hydropower Rich Cases of the Lame duck, Flying Goose and Sitting Duck! - Pun, Santa Bahadur (Hydro Nepal: Journal of Water, Energy and Environment, 2009)
Paraguay has 5.6 million people, Bhutan has 0.6 million and Nepal has 27 million, all small land locked countries with rich hydropower potential. The 12,600 MW Itaipu Project commissioned on Paraguay-Brazil border river, Parana, was the world’s largest hydropower plant until China’s Three Gorges superseded it in 2007. Paraguay’s share, half of Itaipu’s generation, is on average of about 44,000 million units annually with over 90% sold to Brazil. Nepal’s projected average annual generation from three major multipurpose projects, at Sapta Koshi, Karnali Chisapani and Pancheshwar’s 50%, totals about the same. Despite two decades of such large volume of power export, however, Paraguay remains the second poorest country in South America. Nepal, with a tiny 550 MW of hydropower capacity, is undergoing bouts of load shedding and is mired in controversies. Bhutan, with a mere export of about 1,300 MW, comprising 60% of the national revenue, has therefore been strongly recommended as the model for Nepal to replicate. If India is to maintain her 9% GDP growth rate then she will require 785,000 MW (6 times the present installed capacity) of power by 2026/27. Along with this demand for power, she will also need huge quantities of additional freshwater. While there are options for power, there are none for water. All large or small storage projects in Nepal augment water to the rivers flowing down to India. So far India’s policy has been to obtain this augmented water through Nepal’s default. Nepal needs to seriously consider why Paraguay, despite its huge export, is a lame duck while Bhutan with a tiny export is a flying goose! Key words: Power export, Karnali Chisapani, Pancheshwar, Sapta Koshi, Nepal-India Water Resources negotiations, Nepal’s default, Paraguay, Bhutan doi: 10.3126/hn.v3i0.1895 Hydro Nepal: Journal of Water, Energy and Environment Issue No. 3, January, 2008 Page 4-8